Effect of fertility levels on growth and productivity of pearlmillet (Pennisetum glaucum)-based intercropping systems under rainfed condition - Giana, G.K.; Sharma, O.P.; Kuri, B.R.; Shivaran, A.C.; Boori, P.K. (Annals of Agricultural Research, 2016)
A field experiment was conducted during the rainy (kharif) season of 2013 at Jobner, Rajasthan to study the effect of fertility levels on growth, yield and equivalent yield of pearlmillet (Pennisetum glaucum)-based intercropping systems under rainfed condition. The treatments consisted of 4 intercropping systems viz. sole pearlmillet, pearlmillet + clusterbean, pearlmillet + mungbean and pearlmillet + cowpea with 4 fertility levels viz. no fertilizer, 30 kg N + 15 kg P2O5, 45 kg N + 22.5 kg P2O5 and 60 kg N + 30 kg P2O5/ha. The highest plant heights (182.0 cm) of pearlmillet at harvesting stage were recorded with pearlmillet + clusterbean intercropping system. Sole pearlmillet recorded significantly higher effective tillers/plant (2.70), grain (2.04 t/ha) and stover (5.19 t/ha) yields of pearlmillet over pearlmillet intercropped with mungbean and cowpea. Whereas, pearlmillet equivalent yield (36.0 t/ha) and net returns (`45.2 Ã— 103/ha) was observed significantly highest in pearlmillet + clusterbean intercropping system. Fertility level increasing up to 45 kg N + 22.5 kg P2O5/ha were recorded significantly higher growth parameters, yield attributes, grain and stover yields as well as pearlmillet equivalent yield and net returns over control and 30 kg N + 15 kg P2O5/ ha.